(untitled) (Journal of the College of Basic Education, 2023)
The educational process in educational institutions aims to bring about desirable changes in the behavior of the learner, whether this behavior is (cognitive, emotional, or skillful). The art that develops their abilities to creativity and enables them to discover the establishment of capabilities that elevate their artistic reality, which represents the goal that this process reaches through the comprehensive formation of aspects of the learner’s personality. This process works to "qualify the learners and prepare them for a profession that forms part of building society, after providing them with educational experiences and technical skills that help them succeed in their future lives that hinder their lives and perform their jobs in the society in which they live."